1996
DOI: 10.1038/nm0196-90
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine angiogenic vascular prosthesis with bone marrow transplantation

Abstract: Synthetic vascular prostheses are foreign bodies, so that blood coagulation can occur on their luminal surfaces, causing graft occlusion very frequently in prostheses of small diameter. A vascular prosthesis needs angiogenesis for endothelialization of the luminal surface, as endothelial cells have natural and permanent antithrombogenic properties. To induce capillary growth into the graft, we developed a method of transplanting bone marrow cells, which are primitive, strong enough to survive, and create blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(72 citation statements)
references
References 12 publications
2
70
0
Order By: Relevance
“…Elegant studies by Sauvage and colleagues showed that when blood flow is present, implanted synthetic arterial grafts can be reendothelialized even when endothelial cell ingrowth from the anastomoses and the vaso vasorum are apparently prevented (Shi et al, 1994;Wu et al, 1995). Another study found that when bone marrow cells were infiltrated into synthetic vascular grafts, endothelialization occurred more rapidly than in uninfiltrated controls (Noishiki et al, 1996). All of these studies pointed to the presence of hemangioblasts, endothelial cells, or their precursors in the blood and/or bone marrow and provided strong evidence for adult vasculogenesis.…”
Section: Adult Hemangioblasts and Vasculogenesismentioning
confidence: 99%
“…Elegant studies by Sauvage and colleagues showed that when blood flow is present, implanted synthetic arterial grafts can be reendothelialized even when endothelial cell ingrowth from the anastomoses and the vaso vasorum are apparently prevented (Shi et al, 1994;Wu et al, 1995). Another study found that when bone marrow cells were infiltrated into synthetic vascular grafts, endothelialization occurred more rapidly than in uninfiltrated controls (Noishiki et al, 1996). All of these studies pointed to the presence of hemangioblasts, endothelial cells, or their precursors in the blood and/or bone marrow and provided strong evidence for adult vasculogenesis.…”
Section: Adult Hemangioblasts and Vasculogenesismentioning
confidence: 99%
“…12 In light of these reports, we hypothesized that BMCs would contribute to histogenesis in TEVAs. To test this hypothesis, we seeded labeled BMCs onto a biodegradable scaffold, which was then implanted to the inferior vena cava (IVC) of dogs.…”
mentioning
confidence: 99%
“…We used them as the candidate cell for transplantation and as a source of growth factors such as VEGF and b-FGF. 6,7 BMC can be taken easily and autologously. Hamano et al reported that the growth factor from BMC was enhanced under hypoxia, and induced angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…There are several possible reasons for this result. We used BMC as the source of growth factors 6,7 that could induce angiogenesis. The capillary density of group 3 was the greatest in the comparison of all the groups, which suggests that the growth factor in the BMC is involved in the formation of capillary at the border of the damaged myocardium.…”
Section: Discussionmentioning
confidence: 99%